The innovation platform in Mozambique: evidence from Chicualacuala and Changara - Filipe, M. (International Livestock Research Institute, 2010)
As Part of the Livestock Livelihood and Markets Project (LILI Markets), two innovation platforms were implanted in the project sites. First thought to be a mechanism to promote and enhance communication and networking across value chain actors as well as providing them with a platform for addressing common problems the platform, although new, has already surpassed its expected role; it has now become an important element of interaction and problem solving stage among the value chain actors, including the government.